TERHADAP KOMITMEN KERJA PEGAWAI SEKRETARIAT DAERAH KABUPATEN TANAH DATAR - Herru Rachman; Susi Evanita (Jurnal Riset Manajemen Bisnis dan Publik, 2016)
The purpose of this study was to analyze: 1) the effect of fungi leadership on the climate of the organization, 2) Influence of fungi leadership to work commitments, 3) The effect of organizational climate on work commitments. This type of research is the study of causality. This research population is all employees of the Regional Secretariat of Tanah Datar, amounting to 161 people, and the status as civil servants. Total samples 113 people. Data were analyzed using path analysis. The research found that: 1) The function of leadership significantly influence the organizational climate. The existence of better leadership will certainly be able to create a good organizational climate, 2) Function leadership significantly influence the work commitment. The better the leadership function will certainly increase the high work commitment for the employee in performing the task, 3) organizational climate significantly influence the work commitment. The better the organizational climate will certainly increase employee commitment in carrying out the task.  Keywords: Functionality Leadership, Organizational Climate, Work Commitment